JOSÉ DONOSO, TELLING THE TALE AND RECLAIMING THE SOCIAL RESPONSABILITY OF THE ARTIST - Gomez, Juan David (Lingüística y Literatura, 2011)
The Cuban revolution and the military coups in Latin America, among other things, forced Latin American artists committed to addressing the social problems in their countries to consider transforming their social commitment into socialist commitment. This essay shows how Jose Donoso’s novel, Curfew, rejects this call and marks a new stage in the relationship between socialism and American literature by being socially committed to the actual political situation in Chile without being a socialist text.